2023
DOI: 10.3892/or.2023.8549
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of natural polyphenols on colorectal adenomas: Focus on preclinical studies (Review)

Abstract: Colorectal adenoma (CRA) is a premalignant lesion of colorectal cancer. The current treatment is surgical resection, but CRA is prone to recurrence, and there is no safe and effective drug to prevent adenoma recurrence and canceration. Recent studies have shown that natural compounds in plants have favorable antitumor effects. According to preclinical studies, natural polyphenols can regulate different signal pathways and targets to play a role in the treatment of CRA, which is closely related to its inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 146 publications
0
1
0
Order By: Relevance
“…Cancer cells arise due to genetic mutations in suppressor genes or oncogenes [ 108 ]. Polyphenols, by annihilating free radicals, protect the genetic material of the cell from carcinogenesis or other damage [ 101 ].…”
Section: Biopharmaceutical Properties Of Rowanberriesmentioning
confidence: 99%
“…Cancer cells arise due to genetic mutations in suppressor genes or oncogenes [ 108 ]. Polyphenols, by annihilating free radicals, protect the genetic material of the cell from carcinogenesis or other damage [ 101 ].…”
Section: Biopharmaceutical Properties Of Rowanberriesmentioning
confidence: 99%
“…The results showed the evidence that CUR-loaded polymeric nanocapsules inhibit tumor growth (p < 0.00001) and decrease tumor weight (p = 0.0006) in rodents was established. Natural polyphenols, such as apigenin and kaempferol, had therapeutic effects on colorectal adenoma by regulating different signaling pathways and targets [214]. These natural products are all effective and promis-ing candidates for the treatment of cancer and are expected to be introduced into medical practice in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been shown that other significant polyphenols, such resveratrol and curcumin, are active in treating a variety of illnesses. Polyphenols have a variety of physiological functions, including antibacterial, antioxidant, anti-inflammatory, antimalarial, antiviral, antitumor, and immunomodulatory properties [13] , 14 . They may be able to also lessen the oxidative damage of enzymes and DNA in cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are thought to be a significant source of natural medications for management of many diseases because of their exceptional efficacy and safety [ [15] , [16] , [17] ], as evidenced by the various studies that have demonstrated their impact of inhibition on CRC [ 6 , 13 , 14 ]. Nevertheless, there are a number of restrictions on the therapeutic uses of phenolic chemicals.…”
Section: Introductionmentioning
confidence: 99%